Relationship between sarcopenia and orthostatic hypotension. (2nd July 2020) - Soysal, Pinar; Kocyigit, Suleyman Emre; Dokuzlar, Ozge; Ates Bulut, Esra; Smith, Lee; Isik, Ahmet Turan
Abstract: Background: The relationship between sarcopenia and orthostatic hypotension (OH) is unclear. Objectives: The aim of the present study was to investigate associations between sarcopenia/sarcopenia severity and OH. Design: A total of 511 patients attending a geriatric outpatient clinic were included. OH was defined as a decrease in systolic and/or diastolic blood pressure of ≥ 20 mmHg and/or ≥ 10 mmHg, respectively, when one transitions from the supine to an upright position. OH was measured by the Head-up Tilt Table test at 1, 3 and 5 min (OH1, OH3 and OH5, respectively). Sarcopenia and its severity were defined according to the revised European consensus on definition and diagnosis. Results: The mean age of the sample was 75.40 ± 7.35 years, and 69.9% were female. The prevalence of probable sarcopenia, sarcopenia and severe sarcopenia was 42.2%, 6.06% and 11.1%, respectively. After adjustment for all covariates, systolic OH1, OH1 and systolic OH5 were statistically significantly different between severe sarcopenia and the robust group (odds ratio [OR]: 3.26, confidence interval [CI] 0.98–10.84; P  = 0.05 for systolic OH1 ; OR 4.31, CI 1.31–14.15; P  = 0.016 for OH1 ; OR 4.09, CI 1.01–16.55; P  = 0.048 for systolic OH5 ). Only systolic OH1 was statistically different between the sarcopenia and severe sarcopenia groups (OR 2.64, CI 1.87–8.73; P  = 0.012). OH1 and OH5 were statistically significant different between severe sarcopenia and probable sarcopenia groups ( P  < 0.05); there was no relationship between the robust group and probable sarcopenia ( P  > 0.05). Conclusions: There is a close relationship between sarcopenia and severe sarcopenia and OH in older adults. Therefore, when a healthcare practitioner is evaluating an older patient with sarcopenia, OH should also be evaluated, and vice versa.